2021
DOI: 10.2147/cmar.s282684
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Approach to Investigate the Molecular Targets of Sinomenine for Treating Breast Cancer

Abstract: Sinomenine has been known to inhibit the proliferation of breast cancer cells. However, its targets have not been found yet. This study aimed to search for molecular targets of sinomenine for treating breast cancer via network pharmacology. Methods: Potential targets of sinomenine or breast cancer were separately screened from indicated databases. The common targets of both sinomenine and breast cancer were considered as the targets of sinomenine for treating breast cancer. A sinomenine-targetpathway network w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…They finally demonstrated the strong actions of Huangqi decoction against rat liver fibrosis. Furthermore, Li et al [ 110 ] also used the same methodology and revealed the targets of Sinomenine for the treatment of breast cancer.…”
Section: Methodology Of Network Pharmacology Researchmentioning
confidence: 99%
“…They finally demonstrated the strong actions of Huangqi decoction against rat liver fibrosis. Furthermore, Li et al [ 110 ] also used the same methodology and revealed the targets of Sinomenine for the treatment of breast cancer.…”
Section: Methodology Of Network Pharmacology Researchmentioning
confidence: 99%
“…The common targets of disease and drug were calculated by ClusterProfiler package in R software (v3.6.3) to execute GO (gene ontology-biological process) function and KEGG (Kyoto encyclopedia of genes and genomes) pathway enrichment analysis, and p < 0.05 for target Gene screening, analysis of the biological processes and main signal pathways of PTE’s pharmacological effects ( Li XM. et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…He coined the phrase "network pharmacology." [12] The paradigm change from highly specific magic bullet-based drug discovery to multitargeted drug discovery may be made possible by this innovative new technique to drug development. With the help of NP, multigenic complex diseases may find new treatments, and e-therapeutics with ligand formulations tailored to each complicated indication across all disease categories may be developed.…”
Section: Introduction :-mentioning
confidence: 99%